Educating investors about dividends - Andreas Hackethal; Tobin Hanspal; Samuel M. Hartzmark; Konstantin Bräuer (Leibniz Institute for Financial Research SAFE, 2024)
We educate investors with significant dividend holdings about the benefits of dividend reinvestment and the costs of misperceiving dividends as additional, free income. The intervention increases planned dividend reinvestment in survey responses. Using trading records, we observe a corresponding causal increase in dividend reinvestment in the field of roughly 50 cents for every euro received. This holds relative to their prior behavior and a placebo sample. Investors who learned the most from the intervention update their trading by the largest extent. The results suggest the free dividends fallacy is a significant source of dividend demand. Our study demonstrates that simple, targeted, and focused educational interventions can affect investment behavior.
Keywords: G11; G02; D10; 330; Investor education; dividends; free dividend fallacy; educational intervention